Graduates' perception of the Multiprofessional Residence Program in care for women's and children's health (Research, Society and Development, 2022)
Objective: To identify the graduates' perception of the Multiprofessional Residency Program (MRP) in women's and children's health. Methods: This is a descriptive research, with a qualitative approach, carried out in a virtual environment through the Google Meet platform. Thirty-two graduates of the PRM in women's and children's health, from the University of the State of Pará, participated. As a field of action: A medium and high complexity hospital, a reference in the care of high-risk pregnant women and newborns, located in the municipality of Belém do Pará. Graduates were included regardless of the time of completion of the residency. An interview was conducted using a semi-structured script and the data were analyzed using the Iramuteq software. Results: The processing of the corpus was carried out in one second and 2,384 words and 1,258 hapax were identified, with an average per text of 33.79 words, 362 text segments (ST), of which 435 were used, that is, 83 .22% of the total corpus. The software generated, from the Descending Hierarchical Classification, 6 classes expressed in a dendrogram. Final considerations: The perspectives of the graduates were fundamental for obtaining data about professional training in the field of health, expressing the need for adequate tools for evaluation, monitoring and follow-up, with the ability to support the planning of actions to improve the training process, adjustments of incongruities and, therefore, the quality of care provided to the community/patient.